An international database on medical education: the European Medical School Information System (EMSIS) - Eysenbach G; Cloos JM; Jacobsen CT; Antepohl W (Medical Education, 1998)
An electronic database containing the curricula and other information of more than 200 medical schools from 40 different countries has been compiled and made accessible via the World Wide Web (http:@yi.com/emsis), with the aims of providing an overview and to enable a comparison of the curricula of Medical Schools in Europe, of facilitating the cooperation between Medical Schools in Europe and allowing medical students to plan their studying period abroad. The database contains the addresses of medical schools, general information about each medical school (number of students, hospital beds available for teaching, etc.), exchange information (exchange networks the medical school is participating in) and extensive curriculum information, consisting of more than 10,000 course descriptions. All information has largely been entered by the medical schools themselves. Medical schools may update the database directly via the Internet at any time. Users may perform simple queries, for example by country or city, or may perform more complex searches such as 'show all medical schools teaching gynaecology in the fourth year'.